Whistle With a Purpose: Extending Coverage Under SOX to Employees Discharging Their Duties - Jonathan Lee (Washington University Law Review, 2016)
The relative ease with which corporate fraud went unnoticed during the Enron scandal created tension between Congress and the public. In hindsight, the public questioned the difference whistleblowers could have made if they were adequately protected. Since 2002, the Sarbanes-Oxley Act (“SOX”) has provided anti-retaliation protection to employees of publicly traded companies. However, the language used in the whistleblower statute raises the question: Does SOX extend coverage to employees discharging their duties? The district courts have thus far correctly interpreted SOX as extending coverage to employees discharging their duties. Although this issue has only manifested itself in the district courts, it is crucial that Congress remain vigilant—foreseeing the consequences that would arise if courts start to deny whistleblower protection to those best suited to blow the corporate whistle.
Keywords: SOX; whistleblower; Sarbanes-Oxley; employees; coverage